Análise do fluxo de caixa de empreendimentos de transmissão de energia elétrica no mercado brasileiro - Pinto Junior, Roberto Paulo da Silva (2008)
This document presents the market of Brazilian electric energy transmission and its diverse peculiarities. Being a market remunerated just by its availability, the non-availably can cause heavy fines and make the enterprise impracticable. However, energy transmission ventures can receive an additional income, unexpected at the time of project and at the beginning of the commercial transaction. This work can enable us to evaluate the profitability of enterprises in this sector through the description of the costs associated to the enterprise and future gains. The models developed with the aid of the theories of investment analysis and quality in services, as well as the identification of critical factors of the segment, can assist in the choice for the ideal value of prescription to be requested for the company intending to build a transmission line or in the choice of the ideal amount of the investment for the acquisition of transmission line built by another agent. These models can also be used in the estimate of the necessary revenue amount for some known competitor, which can be used as a competitive advantage